CLOTHING, ANALYZER AND METHOD OF MEASURING JOINT ROTATION ANGLE OF SUBJECT - YOSHIDA OSAMU; ONO KENSUKE; HIRATA HITOSHI; YAMADA HITOSHI; IWATSUKI KATSUYUKI; SUZUKI AKIHISA; SHIMODA SHINGO (2019)
To provide a clothing and the like including a fiber type sensor for analyzing rotation angle on each axis of joints having two or more degrees of freedom in a relatively easy manner while maintaining fit-feeling of the subject.SOLUTION: A clothing 200 includes a fiber type sensor 210 in which the capacitance changes as being expanded/contracted in a direction. At least two fiber type sensors 210 are incorporated in the clothing 200 at a position corresponding to a joint in a rotatable manner around at least two axes of a subject when the subject wears the clothing 200 in a manner that the two fiber type sensors 210 are not parallel to each other.SELECTED DRAWING: Figure 1 【課題】被検者の装着感を維持しつつ、２軸以上の自由度を有する関節のそれぞれの軸周りの回動角を比較的容易に解析するための、繊維型センサが備えられた被服等を提供する。【解決手段】一方向へ伸縮されると静電容量が変化する繊維型センサ２１０が備えられた被服２００であって、被検者が被服２００を装着した場合に被検者の少なくとも２軸周りに回動可能な関節に対応する位置に、少なくとも２つの繊維型センサ２１０が互いに平行とならないように組み込まれている。【選択図】図１